Nature-enhancing design of scour protection for monopiles in the North Sea - Groen, Olivier (author) (2019)
A combination of the growth of the offshore wind energy sector and the decline in both species richness and species abundance in the North Sea has inspired the goal to use the scour protection in wind farms as a means to enhance marine life. Present research has focused on general changes which are to be applied to benefit marine life. However, it lacks practical applications of changes to the design of the scour protection and fails to quantify the expected effects of these changes. In this study the extend to which marine life in the North Sea can be enhanced through improvements to the scour protection design for monopiles in wind farms is researched by comparing the habitat suitability in three situations (North Sea in absence of wind farms, North Sea with wind farms and scour protections as currently designed, and wind farms with enhanced scour protections) for four indicator species (Atlantic cod, European lobster, flat oyster, and the Ross worm). For the third situation (the enhanced scour protections), several habitat enhancements as well as some stock enhancements have been proposed and their expected effects and costs have been studied. The availability of hard substrate and the absence of (seabed disturbing) fisheries is what makes wind farms suitable compared to a sandy sea bed. These habitats can be further improved by using a large and narrow grading to provide shelter and stable attachment material and by placement of additional elements such as piles of rock, (concrete) tubes, and shell filled nets. Species which are not likely to successfully colonize the wind farm, such as the European lobster and flat oyster, are to be introduced by humans through stock enhancements. Civil Engineering | Structural Engineering | Hydraulic Structures